(untitled) (Journal of Bio-Science, 2023)
The present study evaluated the potentiality of cage culture of stinging catfish (Heteropneustes fossilis) under different feeding regimes. Fish experiments were consists of three treatments (T1, T2 and T3), each with three replicates, and lasted for 90 days. The stocking density was 300 fry ( 1.5 g) per cage. Fish were given commercial floating feed (28% crude protein) twice daily (in the morning and evening) at 5% (T1), 7% (T2) and 9% (T3) of body weight. Water quality parameters were monitored fortnightly. Mean values of water quality showed no significant difference among the treatments. Survival of stinging catfish was comparatively higher with T2 (83.1%) compared to T1 (81.6%) and T3 (79.3%). The specific growth rate was significantly higher in fish reared underT2 treatment than T1 and T3, corresponding to 1.91, 1.85 and 1.87% bwd-1, respectively. The net yield was also highest with T2 (1.74 kg) than those with T1 (1.57 kg) and T3 (1.60 kg). These data together with cost-benefit analysis among three treatments suggests that 7% feeding rate positively influence growth and production offish. Therefore, a daily feeding at 7% of body weight can be suitable for culturing stinging catfish in cages. J Bio-Sci. 30(1): 01-09, 2022 (June)